MARKETING RESEARCH WITH BLOCKCHAIN CONCEPTS FOR LEARNING OUTCOMES – RESEARCH AND SYSTEM THINKING SDG#4 AND 9. - Yeung, Shirley; Zhou, Ceci (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2025)
The purpose of this paper is to explor the steps of applying GLD and QF Level 5 domains to assess the competency level of business undergraduate students’ research thinking and system thinking for sustainable development of a research-based course of a QF Level 5 business programme. This paper is to explore the steps of assessing business students on current issues identification for PILOs and CILOs with Generic Level Descriptors (GLD) and AI rubrics. This is managerial relevant to curriculum planning and assessment design. However, quantitative and qualitative research for an assessment framework on QF/ GLD AI rubrics is needed for competency building of business research students.